Pinta: The uGMRT data processing pipeline for the Indian Pulsar Timing Array. (14th April 2021) - Susobhanan, Abhimanyu; Maan, Yogesh; Joshi, Bhal Chandra; Prabu, T.; Desai, Shantanu; Nobleson, K.; Susarla, Sai Chaitanya; Girgaonkar, Raghav; Dey, Lankeswar; Batra, Neelam Dhanda; Gupta, Yashwant; Gopakumar, A.; et al.
Abstract: We introduce pinta, a pipeline for reducing the upgraded Giant Metre-wave Radio Telescope (uGMRT) raw pulsar timing data, developed for the Indian Pulsar Timing Array experiment. We provide a detailed description of the workflow and usage of pinta, as well as its computational performance and RFI mitigation characteristics. We also discuss a novel and independent determination of the relative time offsets between the different back-end modes of uGMRT and the interpretation of the uGMRT observation frequency settings and their agreement with results obtained from engineering tests. Further, we demonstrate the capability of pinta to generate data products which can produce high-precision TOAs using PSR J1909 $-$ 3744 as an example. These results are crucial for performing precision pulsar timing with the uGMRT.